All‐Carbon Photodetectors: Highly Sensitive Broadband Single‐Walled Carbon Nanotube Photodetectors Enhanced by Separated Graphene Nanosheets (Advanced Optical Materials 23/2018). Issue 23 (4th December 2018) - Cai, Baofang; Su, Yanjie; Tao, Zejun; Hu, Jing; Zou, Cheng; Yang, Zhi; Zhang, Yafei
Abstract : Yanjie Su and co‐workers (article number1800791 ) demonstrate a proof‐of‐concept all‐carbon hybrid photodetector using single‐walled carbon nanotube (SWNT)/separated graphene (SGR) Schottky junctions, exhibiting ultrahigh‐responsivity and microsecond and broadband photoresponse. The charge transfer dynamics at the planar SWCNT/SGR Schottky junctions are investigated by combining Raman spectra under different bias voltages with current–voltage curves.